2014
DOI: 10.1021/ac501075f
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Identification of Clinically Relevant Microorganisms Using Rapid Evaporative Ionization Mass Spectrometry

Abstract: Rapid evaporative ionization mass spectrometry (REIMS) was investigated for its suitability as a general identification system for bacteria and fungi. Strains of 28 clinically relevant bacterial species were analyzed in negative ion mode, and corresponding data was subjected to unsupervised and supervised multivariate statistical analyses. The created supervised model yielded correct cross-validation results of 95.9%, 97.8%, and 100% on species, genus, and Gram-stain level, respectively. These results were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 45 publications
0
113
1
Order By: Relevance
“…Detailed sampling schedules can be found in Table S Earlier studies demonstrated that REIMS is suitable to generate phospholipid profiles of various biological materials such as animal tissues, 2,27,28 human ex-vivo tissue samples of healthy and cancerous origin, 1,29 as well as microorganisms. 3,30 As analysis is performed in negative ion mode, the spectral content is similar to that described in those earlier studies featuring predominantly glycerophospholipidtype membrane lipids such as phosphatidylethanolamines -ions. A list of spectral features above a relative abundance of 2.5% with molecular assignments can be found in Table S-5.…”
Section: Robustness Of Reims Spectral Profilesmentioning
confidence: 72%
See 1 more Smart Citation
“…Detailed sampling schedules can be found in Table S Earlier studies demonstrated that REIMS is suitable to generate phospholipid profiles of various biological materials such as animal tissues, 2,27,28 human ex-vivo tissue samples of healthy and cancerous origin, 1,29 as well as microorganisms. 3,30 As analysis is performed in negative ion mode, the spectral content is similar to that described in those earlier studies featuring predominantly glycerophospholipidtype membrane lipids such as phosphatidylethanolamines -ions. A list of spectral features above a relative abundance of 2.5% with molecular assignments can be found in Table S-5.…”
Section: Robustness Of Reims Spectral Profilesmentioning
confidence: 72%
“…1,3 To test the general hypothesis that REIMS spectral patterns are reproducible and sufficiently specific to differentiate between different human cancer cell lines, three different cell lines (HeLa -cervical adenocarcinoma, MES-SA -uterine sarcoma, and SNB-19 -glioblastoma) were analyzed in an experiment designed to test spectral reproducibility. The experimental scheme depicted in Figure S…”
Section: Robustness Of Reims Spectral Profilesmentioning
confidence: 99%
“…Also, mass spectrometers should provide a sufficiently good mass accuracy and resolution to obtain a low number of false positive peak annotations. If the ionization methods are the same but different mass spectrometers are used, peak annotation step and application of scaling factors might not be necessary [39].…”
Section: Cross-platform Normalization Methodsmentioning
confidence: 99%
“…This MALDI-TOF-MS approach is applied worldwide as a routine identification tool for typing and identifying microbial species in clinical microbiology laboratories and is known as Biotyper ™ [30]. For this purpose, alternative ambient ionization methods are also applied, such as rapid evaporative ionization MS (REIMS) [31]. In both approaches, the accurate identification of unknown microorganisms is achieved by comparing protein profiles obtained from cultured colonies to spectra in a library without any a priori knowledge [32][33][34].…”
Section: Protein Applications In Clinical Msmentioning
confidence: 99%